Human papillomavirus (HPV) genotype distribution in Malaysia: A systematic review - Cassandra Sheau Mei, Chee; Melissa Lim, Siaw Han; Pei, Jye Voon; Yolanda, Augustin; Sanjeev, Krishna; Nafeesa, Mat Ali; Izzati Binti, Wan Maharuddin; Khairiyah Binti, Abdul Rahim; Adam Malik, Ismail; Edmund Sim, Ui Hang; Paul Cliff Simon, Divis; Timothy Adrian, Jinam; et al. (Springer Nature, 2025)
Background: Human papillomavirus (HPV) is a key etiological factor in cervical cancer in both Malaysia and globally. It continues to pose a significant public health challenge. This systematic review aims to delineate the distribution of HPV genotypes across different demographics in Malaysia to inform targeted prevention strategies.